2020
DOI: 10.3390/nu12041162
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Nutritional Qualities of Supermarket’s Own and Regular Brands of Bread in Sweden

Abstract: Processed food is associated with unhealthy qualities such as higher content of harmful fats, sugars and salt. The aim of our study was to compare the nutritional qualities of supermarket’s own brands and regular brands of bread sold in Sweden. Additionally, we compared the nutritional qualities of gluten-free and gluten-containing bread. We collected information from the labels of 332 bread products available in the largest grocery store chains. The Australian Health Star Rating (HSR) system was used to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
(44 reference statements)
1
7
0
1
Order By: Relevance
“…The amount of carbohydrates was about 43.7% for GR samples, while, in WM samples, it was about 42.0%. The level of proteins, ash, fats, TDF and carbohydrates were in line with those reported for different bread and breadlike products [ 30 , 31 , 32 ]. The amount of carbohydrates converted into simple sugars during sprouting and baking are reported in Table 1 .…”
Section: Resultssupporting
confidence: 88%
“…The amount of carbohydrates was about 43.7% for GR samples, while, in WM samples, it was about 42.0%. The level of proteins, ash, fats, TDF and carbohydrates were in line with those reported for different bread and breadlike products [ 30 , 31 , 32 ]. The amount of carbohydrates converted into simple sugars during sprouting and baking are reported in Table 1 .…”
Section: Resultssupporting
confidence: 88%
“…Values are presented as mean ± standard deviation and are followed by different letters (a-e) in the same column, which show significant differences (p < 0.05). 1 (n = 3), 2 (n = 6), 3 (n = 52). Brown sorghum (BS) flour and water (W) are presented as coded levels of the 2 2 factorial design, and as real levels on a flour weight basis.…”
Section: Effects Of Ingredients On the Physical-chemical And Sensory Characterisctics Of Gfbmentioning
confidence: 99%
“…Several studies concerning the gluten-free bread (GFB) available on the market have shown low levels of protein and micronutrients and high levels of lipid and sodium compared to similar products made with wheat flour. These features, in addition to the lack of enrichment or fortification, negatively contribute to the health of individuals with a gluten-restricted diet [1][2][3][4][5][6]. Our recent overview showed that over the last ten years, multiple gluten-containing (GC; n = 7122) and gluten-free (GF; n = 3153) food products have been investigated and compared worldwide [1].…”
Section: Introductionmentioning
confidence: 99%
“…They found no differences in total energy and protein, fat, and total carbohydrates for most food categories, including breakfast cereals, cereal bars, biscuits, cakes and tarts, bread and bread products, and pasta ( 20 ). By considering the single packaged bread category, a recent Swedish study found a slightly higher nutritional quality, in terms of higher protein, lower total fat, and lower sugar, of PL items than the BR ones ( 21 ).…”
Section: Discussionmentioning
confidence: 99%